(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Investments in Equity markets become a common phenomenon for all individuals. The national economic growth majorly depends upon the development of equity markets in the nation. Developments in the financial markets around the globe are providing a wide variety of markets and investment options to the investor’s. Investment decision making is not an easy task it includes lot of analysis. Research has been done to know the factors influencing the investment decisions of the investors. Primary data is gathered through a structured questionnaire. Sample size for the study is 100 respondents from Coimbatore district. In this study, data was analyzed using percentages and Ranking method. It is found that currency strength (economic factors), legal aspect of the company (industry factors), legacy of the company (Reputation factors) and new products of the company (positioning factors) are influencing the investment decisions. The findings from this study would helpthe policy makers and corporate before making any major decisions.